The Proportion of Human Immunodeficiency Virus Patients in Circumcised and Uncircumcised Men with Unsafe Sexual Practices in Special Care Center in General Hospital Center Haji Adam Malik Hospital Medan - -, Juliyanti; Rangkuti, Irwan Fahry; Siregar, Remenda (Indonesian Journal of Medicine, 2017)
Background: The incidence of HIV was found to be higher in uncircumcised men compared to circumcised men. Circumcision was known to protect and fight against the acquired HIV infection. HIV infection was classified into sexual transmitted infections since it is mostly transmitted sexually (95%). The risk was higher in unsafe sexual practices, such as having multiple sexual partners and not using protections like condoms.Subjects and methods: This was a descriptive study with cross-sectional design study. There were 340 patients who came to the special care center in General Hospital Center Haji Adam Malik Hospital and participated in this study. Data such as history taking and clinical examination were then collected.Result: The proportion of HIV patients with unsafe sexual practices was lower in circumcised men group, which was 141 patients (41.5%), compared to uncircumcised men group which was 199 patients (58.5%).Conclusion: The proportion of HIV infection in uncircumcised men with unsafe sexual practices was higher than in circumcised men.Keywords: HIV, Circumcision, Sexual practiceCorespondence:ÃÂ Juliyanti. Department of Dermato-veneorology, Faculty of Medicine, University of North Sumatera, Indonesia. Mobile: 082174346045Indonesian Journal of Medicine (2017), 2(2): 94-99https://doi.org/10.26911/theijmed.2017.02.02.03